ANALISIS PENGARUH LABELISASI HALAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK MAKANAN IMPOR DALAM KEMASAN PADA MAHASISWA KEDOKTERAN UNIVERSITAS SUMATERA UTARA - Dewi Kurni Sari; Ilyda Sudardjat (Ekonomi dan Keuangan, 2013)
This wacthfulness internal issue formulation how does influence labeling rightful towards import food product purchasing decision in package in field University of North Sumatra. Hypothesis in this watchfulness found connection between labeling rightful with import food product purchasing decision in package in field University of North Sumatra Medan. Method that used in influence analysis labeling rightful towards import food product purchasing decision in package in field University of North Sumatra Medan Rank Correlation Coefficient by using analyzer to managed data that is by using SPSS 17. Based on Correlation Analysis Result Spearman Rank show that: Value Sig 0,025 < 0,05 so Medan. This watchfulness aims to detect “Influence Analysis Labeling Rightful Towards Import Food Product Purchasing Decision in Package in Field University of North Sumatra Medan”. As to free variable in this watchfulness labeling rightful and as bound variable import food product purchasing decision in package.ha accepted, ho aversed, so there connection between labeling rihtful with import food product purchasing decision in package, with confidence level 95% (positive correlation).Keyword: Labeling Rifhtful, Import Food Product Purchasing Decision in Package.